OP0141 #X00A0; CD28 AS A POTENTIAL THERAPEUTIC TARGET FOR GIANT CELL ARTERITIS. (June 2019) - Watanabe, Ryu; Zhang, Hui; Berry, Gerald; Nadler, Steven; Goronzy, Jörg; Weyand, Cornelia
Abstract : Background: Giant cell arteritis (GCA) is a granulomatous vasculitis of medium and large arteries. In GCA-affected arteries, vascular wall is destroyed by tissue-infiltrating CD4 T cells and macrophages, which leads to intramural neoangiogenesis, intimal hyperplasia and luminal occlusion. Objectives: This study aimed to examine how CD28 signaling plays a role in vasculitis induction and maintenance and which pathogenic processes are dependent on CD28-mediated T-cell activation. Methods: We engrafted human arteries into immunodeficient NSG mice and induced vasculitis by transferring GCA immune cells. Human artery-NSG chimeras were treated with anti-CD28 domain antibody or control Ab. Using tissue transcriptome analysis, immunohistochemistry, flow cytometry and immuno-metabolic analysis, treatment effects were examined in vivo and in vitro. Results: Treating such humanized mice with an anti-CD28 domain antibody profoundly reduced tissue-infiltrating T-cells and effectively suppressed vasculitis. Mechanistic studies revealed that CD28 regulated AKT signaling, T-cell proliferation and differentiation of IFN-γ and IL-21-producing effector T-cells. Blocking CD28 signaling disrupted T-cell metabolic fitness; particularly, glucose utilization. Expression of the glucose transporter Glut1 and of glycolytic enzymes as well as mitochondrial oxygen consumption all rely on CD28 signaling. CD28 blockade effectively suppressed vessel wall remodeling processes such as adventitial microvessel formation and intimal hyperplasia as well as induction and maintenance of CD4 + CD103 + tissue-resident memory T cells. Conclusion: CD28 stimulation provides a metabolic signal required for pathogenic effector functions in GCA, implicating CD28 signaling as a promising therapeutic target. References: [1] MMP (Matrix Metalloprotease)-9-Producing Monocytes Enable T Cells to Invade the Vessel Wall and Cause Vasculitis. [2] Watanabe R, Maeda T, Zhang H, Berry GJ, Zeisbrich M, Brockett R, Greenstein AE, Tian L, Goronzy JJ, Weyand CM. [3] Circ Res. 2018 Aug 31;123(6):700-715. [4] Inhibition of JAK-STAT Signaling Suppresses Pathogenic Immune Responses in Medium and Large Vessel Vasculitis. [5] Zhang H, Watanabe R, Berry GJ, Tian L, Goronzy JJ, Weyand CM. Circulation. 2018 May 1;137(18):1934-1948. Acknowledgement: This work was supported by a sponsored research agreement with Bristol-Myers Squibb. Disclosure of Interests: Ryu Watanabe: None declared, Hui Zhang: None declared, Gerald Berry: None declared, Steven Nadler Employee of: Bristol-Myers Squibb, Jörg Goronzy: None declared, Cornelia Weyand: None declared